Terra Incognita : Poems - Henning, Sara (Book collections on Project MUSE., 2022)
"This poignant collection of masterful elegies centers on the revelatory ways in which the speaker reconciles love, loss, and grief's legacy. Following her mother's battle with colon cancer and her own crisis of meaning, Henning culminates the collection with her rediscovery of joy in life's small moments"--